NETWORK TOPOLOGIES - Singh, Pankaj; Verma, Shubham (IJRDO -Journal of Computer Science Engineering, 2015)
The geometrical arrangement of computer resources, remote devices and communication facilities is known as Network structure or Network topology. A computer network is comprised of nodes and links, a node is the end point of any branch in a computer, a terminal device, workstation or interconnecting equipment facility. A link is a communication path between two nodes. The terms “circuit” and “Channel” are frequently used as synonyms for the link. There are different types of the topologies like bus, ring, tree, mesh etc.